2015
DOI: 10.4025/actascibiolsci.v37i2.26067
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>In vitro</i> germination, callus induction and phenolic compounds contents from <i>Pyrostegia venusta</i> (Ker Gawl.) Miers

Abstract: ABSTRACT.A protocol for the in vitro germination and callus induction in Pyrostegia venusta, a medicinal plant species from the Brazilian savannah (Cerrado) is provided. The establishment of cultures of P. venusta was originally obtained from seeds germinated in vitro and induced callus directly from leaf explants of seedlings. Seeds were germinated on MS and WPM media containing 100 and 50% of salt concentration, supplemented with 30 g L Germinação in vitro, indução de calos e teores de compostos fenólicos em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
2
5
0
3
Order By: Relevance
“…However, in the present study, callus growth and fresh weight were inversely related to the tested phenolic compound's concentration. A similar observation was also recorded by Braga et al [56], in which a higher concentration of phenolic compounds suppressed the growth of callus and its biomass. The inhibitory effects of these compounds on the biomass of all weed calli were observed in leaf extraction concentrations as low as 10 −5 M. Previous studies reported a close association between allelopathic properties and phytochemical exudes from plants [57,58].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, in the present study, callus growth and fresh weight were inversely related to the tested phenolic compound's concentration. A similar observation was also recorded by Braga et al [56], in which a higher concentration of phenolic compounds suppressed the growth of callus and its biomass. The inhibitory effects of these compounds on the biomass of all weed calli were observed in leaf extraction concentrations as low as 10 −5 M. Previous studies reported a close association between allelopathic properties and phytochemical exudes from plants [57,58].…”
Section: Discussionsupporting
confidence: 88%
“…The inhibitory effects of these compounds on the biomass of all weed calli were observed in leaf extraction concentrations as low as 10 −5 M. Previous studies reported a close association between allelopathic properties and phytochemical exudes from plants [57,58]. The allelochemicals released from the plant exudes usually inhibit the growth of plant cells by disrupting the cell membrane and cellular components [56]. Phenolic compounds such as p-coumaric acid and its various derivatives were found to inhibit photosynthesis enzymatic activities of glucosephosphate isomerase (PGI), 6-phosphate dehydrogenase (G6P-DH), and aldolase (AID) in the oxidative pentose phosphate pathway (OPPP), causing a detrimental effect on plant growth [59].…”
Section: Discussionmentioning
confidence: 92%
“…A inoculação se deu em tubos contendo 15 mL de meio MS basal (MURASHIGE; SKOOG, 1962), suplementado com 30 g L -1 de sacarose e solidificados com 7 g L -1 de agar com o pH ajustado para 5,8±0,1. Os tubos foram transferidos para sala de crescimento a 25±1 o C, fotoperíodo de 16 horas e densidade de fluxo de fótons fotossinteticamente ativos de 35 µmol m -2 s -1 (BRAGA et al, 2015).…”
Section: Germinação In Vitrounclassified
“…A germinação iniciou a partir do 15° dia após a inoculação, com o desenvolvimento do primeiro par de folíolos a partir do 21° dia. Padrão similar para a germinação in vitro de P. venusta foi descrito por Braga et al (2015). Estes autores sugerem que plântulas de P. venusta não são exigentes quanto às necessidades nutricionais para seu desenvolvimento inicial, bastando a suplementação oferecida pelo meio MS (MURASHIGE; SKOOG, 1962).…”
Section: Germinação In Vitrounclassified
“…The most commonly used disinfectants are the ethanol and the compounds based on Cl, such as sodium hypochlorite (NaClO) and calcium hypochlorite (Ca(ClO) 2 ) (Donini et al 2005;Braga et al 2015;Pereira et al 2015). The employment of NaClO, having as a source commercial bleach (CB) in the disinfestation of seeds and culture media, proves to be an efficient and low cost method and the product easy to purchase (Rodrigues et al 2012).…”
Section: Introductionmentioning
confidence: 99%